2023
DOI: 10.3390/agriculture13020252
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of BTB Domain-Containing Gene Family in Grapevine (Vitis vinifera L.)

Abstract: BTB (broad-complex, tram track and bric-a-brac) proteins have broad functions in different growth processes and biotic and abiotic stresses. However, the biological role of these proteins has not yet been explored in grapevine, which draws our attention towards the BTB gene family. Herein, we identified 69 BTB genes (VvBTB) in the Vitis vinifera genome and performed comprehensive in silico analysis. Phylogenetic analysis classified VvBTB proteins into five groups, and further domain analysis revealed the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…The analysis of the cisacting elements of the PfBTB genes promoter revealed the presence of light-responsive elements, stress-responsive elements, and hormone-responsive elements (Figure 4). Among them, light-responsive elements are ubiquitous and most abundant, which is consistent with the analysis results of different species of grape [34], sugar beet [35], and tomato [5], indicating that the transcriptional regulation of PfBTB may be generally affected by light signals. Meanwhile, hormone-responsive elements, such as SA, GA, IAA, MeJA, and ABA, were also contained on the PfBTB gene promoter.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The analysis of the cisacting elements of the PfBTB genes promoter revealed the presence of light-responsive elements, stress-responsive elements, and hormone-responsive elements (Figure 4). Among them, light-responsive elements are ubiquitous and most abundant, which is consistent with the analysis results of different species of grape [34], sugar beet [35], and tomato [5], indicating that the transcriptional regulation of PfBTB may be generally affected by light signals. Meanwhile, hormone-responsive elements, such as SA, GA, IAA, MeJA, and ABA, were also contained on the PfBTB gene promoter.…”
Section: Discussionsupporting
confidence: 85%
“…The number of BTB family members in plants varies greatly among different species: 69 members in grape [ 34 ], 49 members in sugar beet [ 35 ], 38 members in tomato [ 5 ], and 158 members in rice [ 4 ]. Using the recent determination of the P. fortunei genome, we identified 62 BTB members for the first time in Paulownia ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present work focused on identifying and characterizing the BTB gene family across the genome of S. tuberosum. As per earlier studies, the number of BTBs identified were 77 in A. thaliana [4], 38 in Solanum lycopersicum [39], and 69 in Vitis vinifera [40]. We identified a total of 57 BTBs in the potato genome.…”
Section: Discussionsupporting
confidence: 69%